NASIRUDDIN TUSI AND HIS PLACE IN THE HISTORY OF CIVILIZATION OF THE PEOPLES OF THE EAST - Norkuchkarov Sherali Shavkatzoda (Galaxy International Interdisciplinary Research Journal, 2021)
The article examines the role of Nasiruddin Tusi - "Master-ul-Bashar" in the science and culture of the peoples of the East in the XIII century, and the content of the works created by the thinker. The weight of the author’s scientific works was highlighted during his lifetime, as well as their scientific significance today and the effectiveness of his work. In addition, some literary-scientific and socio-political issues of the 13th century Mongol khanate, which are related to the life and work of the scientist, are analyzed. The author’s research in various fields and their content are illustrated with examples.